2016
DOI: 10.18632/oncotarget.11685
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of PDL1 expression in pancreatic cancer

Abstract: Pancreatic cancer is one of the most aggressive human cancers. PD1/PDL1-inhibitors recently showed promising results in different cancers with correlation between PDL1 tumor expression and responses. Expression of programmed cell death receptor ligand 1 (PDL1) has been scarcely studied in pancreatic cancer. In this retrospective study, we analyzed PDL1 mRNA expression in 453 clinical pancreatic cancer samples profiled using DNA microarrays and RNASeq. Compared to normal pancreatic samples, PDL1 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 77 publications
(86 reference statements)
9
54
2
Order By: Relevance
“…This has already been reported in several cancers, 15,58,[62][63][64][65][66] although a favorable prognostic value has been reported in other cancers. 50,55,59,[67][68][69] For comparison and to our knowledge, only four studies-three publications 8,15,42 and one meeting presentation 70 -have described PDL1 expression and clinicopathological correlations in STS.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This has already been reported in several cancers, 15,58,[62][63][64][65][66] although a favorable prognostic value has been reported in other cancers. 50,55,59,[67][68][69] For comparison and to our knowledge, only four studies-three publications 8,15,42 and one meeting presentation 70 -have described PDL1 expression and clinicopathological correlations in STS.…”
Section: Discussionmentioning
confidence: 63%
“…In these cases, PDL1 was upregulated likely because of a negative feedback loop that follows cytotoxic cells activation, notably through the production of IFNg, a known regulator of PDL1 expression. In contrast, PDL1 expression was unfavorable in pancreatic carcinoma, 66 where expression was associated with a less strong cytotoxic profile than in breast cancer and GISTs and with several signs of T-cell exhaustion, with enrichment in inhibitory molecules and pro-tumor populations (Tregs, myeloid-derived suppressor cells), and downregulation of most MHC class-I members suggesting a defect in antigen presentation. In the present study, the PDL1-high signature suggested a strong cytotoxic T-cell response, without defect in antigen presentation or enrichment in inhibitory molecules and pro-tumor populations, but with some degree of T-cell exhaustion and negative regulation of Tcell response.…”
Section: Discussionmentioning
confidence: 93%
“…PD-L1 expression by tumor cells has been associated with a poorer prognosis or advanced disease (20, 3436). About 80% of PC cases express PD-L1, of which 20% have up-regulated expression of PD-L1 (compared to normal pancreatic tissue) and tend to be highly invasive and recurrent (37, 38). …”
Section: Resultsmentioning
confidence: 99%
“…CTLA4 and PD-1 pathways are the two negative co-stimulatory pathways mediating immunosuppression in a diversity of cancer types, including melanoma, ovarian and lung cancers(41). In pancreatic cancer, over-expression of PDL-1 results in lymphocyte exhaustion, down-regulation of most MHC class I members, and is associated with shorter disease-free survival and overall survival(42). Moreover, PAAD is a heterogeneous disease involving types of molecular and cellular pathways.…”
Section: Discussionmentioning
confidence: 99%